Agglomeration and specialisation patterns of Finnish biotechnology - On the search for an economic rationale of dispersed industry structure - Antti-Jussi Tahvanainen; Raine Hermans (The Research Institute of the Finnish Economy (ETLA), 2008)
This study sets out to inspect empirically whether existing theory in Geographical Economics (GE) is able to provide a rationale for the controversial and much debated structure of the highly knowledge- and research-intensive biotechnology industry in Finland. In addition to providing evidence of GE in action, we integrate the effects that active public technology policy might have on geographic structures of industries into our analysis as a novel discourse. The results provide evidence of a theory based rationale that is able to deepen our understanding of the roles that different regions have enacted in the development of the case industry. Simultaneously, however, the rationale also reveals several challenges that different types of regions still have to overcome in order to steer on a track of sustainable economic development in the future. Based on the results we argue that public sector funding has enabled certain regions to develop in ways that otherwise would not be sustainable.
Keywords: 330; Geographical economics; regional agglomeration; regional specialisation; regional integration; Biotechnische Industrie; Klein- und Mittelunternehmen; Regionale Konzentration; Regionale Arbeitsteilung; Forschungs- und Technologiepolitik; Neue ökonomische Geographie; Finnland